PPH PASAL 23 – MASA FEBRUARI 2017 ( STUDI KASUS PADA PT ELNUSA FABRIKASI KONSTRUKSI JAKARTA ) - Setiadi, Setiadi (Feb Universitas Dirgantara Marsekal Suryadarma, 2019)
Article 23 Income Tax, which is the tax imposed on Services and Leases made by a company. The research object itself is engaged in maintenance services for oil & gas equipment and construction equipment construction. Article 23 Income Tax on Services and Leases made by a company is calculated based on DPP or gross income from the value of Services or Rent, Deposit of Income Tax Article 23 through a Perception Bank or registered Tax Office on the 10th of the following month after the tax period ends. After that, the Article 23 Income Tax SPT Report is carried out on the 20th of the following month after the tax period ends. If there is a delay in Deposit and Reporting, and Recording is in accordance with applicable accounting standards